Factors influencing financial risk tolerance: A review - Mubarokah, Bunyamin; Norwazli, Abdul Wahab (Penerbit Universiti Malaysia Pahang, 2021)
High financial risk tolerance level encourages investors’ participation in financial market. Thus, elevate their capabilities to achieve their financial goals and support national economic growth and well-being. This paper aims to investigate the factors affecting financial risk tolerance from studies around the globe. A comprehensive review of financial risk tolerance is carried out with a particular attention on factors that impact financial risk tolerance on financial decisions. This study indicates that financial risk tolerance can be explained by demographic profiles, psychology, social, geographical differences, and financial capability factors. These findings will be useful to professionals, technologists, and financial institutions to identify potential investors based on the indicators concluded with the suggestion on financial technology (FinTech) utilisation. Hence, encouraging participation in the Malaysian financial market during global health crisis and reaching economic well-being towards industrial revolution 4.0 (IR 4.0).